Spatial distribution of soil nematodes relates to soil organic matter and life strategy. (September 2019) - Quist, Casper W.; Gort, Gerrit; Mooijman, Paul; Brus, Dick J.; van den Elsen, Sven; Kostenko, Olga; Vervoort, Mariette; Bakker, Jaap; van der Putten, Wim H.; Helder, Johannes
Abstract: Soils are among the most biodiverse and densely inhabited environments on our planet. However, there is little understanding of spatial distribution patterns of belowground biota, and this hampers progress in understanding species interactions in belowground communities. We investigated the spatial distribution of nematodes, which are highly abundant and diverse metazoans in most soil ecosystems. To gain insight into nematode patchiness, we mapped distribution patterns in twelve apparently homogeneous agricultural fields (100 m × 100 m each) with equal representation of three soil textures (marine clay, river clay and sandy soil). Quantitative PCRs were used to measure the abundances of 48 distinct nematode taxa in ≈1200 plots. Multivariate analysis showed that within this selection of sites, soil texture more strongly affected soil nematode communities than land management. Geostatistical analysis of nematode distributions revealed both taxon-specific and field-specific patchiness. The average geostatistical range (indicating patch diameter) of 48 nematode taxa in these fields was 36 m, and related to soil organic matter. Soil organic matter content affected the spatial variance (indicating within-field variation of densities) in a life-strategy dependent manner. The r-strategists (fast-growing bacterivores and fungivores) showed a positive correlation between organic matter content and spatial variance, whereas most K-strategists (slow-growing omnivores and carnivores) showed a negative correlation. Hence, the combination of two parameters, soil organic matter content and a general life-strategy characterisation, can be used to explain the spatial distribution of nematodes at field scale. Highlights: Nematode distribution maps show taxon- and field-specific levels of patchiness Distributions of nematodes with similar food preferences show little or no overlap Soil organic matter affects nematode patchiness in a life-strategy dependent manner Stochasticity is a dominant driving factor for mesoscale distribution of nematodes Distribution maps enable the design of soil sampling schemes with known accuracies